STUDY OF LEGAL REGULATION enforcement proceedings from past to present - Бородін, І. Л. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In the article are examined the problems of introduction of the legal and organizational providingof implementation of decisions and decisions of court (judges) in Ukraine, as a result of analysisof normatively legal acts, suggestions are made in relation to the improvement of the activityof organs (public servants) of executive service of Ukraine.